Analysis Of Students’ Conceptual Understanding Assisted By Multirepresentation Teaching Materials in the Enrichment Program - Susilaningsih, Endang; Fatimah, Siti; Nuswowati , Murbangun (KnE Social Sciences, 2019)
Thispurposeofthisresearchwastodeterminethestudents’conceptualunderstanding assisted by acid-base multi-representation teaching materials in the enrichment program. The type of research was case study that used combination of qualitative and quantitative methods by involving 49 second grade science students of State High School in Kudus who have passed/completed acid-base material. The sampling technique was carried out by purposive sampling. Conceptual understanding was analyzed using reasoned questions, namely three tier multiple choice test as pretest andposttest.Theresultsshowedthatstudents’conceptualunderstandingofacid-base material was considered as high category. Achievement of students’ conceptual understandinghasincreased,asseenfromtheresultsofstudents’pretestandposttest namely from 37% to 71%. Overall, enrichment learning assisted by multi-representation teaching materials is effective when used in learning so that the achievement of students’ conceptual understanding of acid and base material is categorized as high category. Keywords: teaching material; multi representation; conceptual understanding; enrichment program.